Sistema de comercialización de productos alimenticios frescos y procesados - García García, Hernán Mauricio (2022)
The present study is a bibliographic review on the problem of the commercialization of fresh and processed foods in the world, in the country, a review was also made of the types and classification of fresh and ultra-processed foods, as well as their safety following the quality standards, its requirements and demands for safe consumption, in the same way as to reach its traceability and be able to detect on the spot if there are problems of any contamination to be able to stop and identify where or in what part of the chain of production was the contamination and stop that alteration and that it does not continue affecting potential consumers, A review was also carried out on which authorities have jurisdiction over the commercialization of these foods in the cities, and what problems arise and improve a proposal on infrastructure and how to commercialize these foods, finally, it was broken down or commented on the problem of marketing in Peru, and the amount of waste caused by these products in the Victoria District stop in the country's capital. For which recommendations were made to improve this latent problem somewhat not only in Peru, but throughout Latin America and the Caribbean.